2019
DOI: 10.1590/2175-8239-jbn-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of delayed graft function duration on function and survival of deceased donor kidney transplants

Abstract: Introduction: Delayed graft function (DGF) is a frequent complication after deceased donor kidney transplantation with an impact on the prognosis of the transplant. Despite this, long-term impact of DGF on graft function after deceased donor kidney transplantation has not been properly evaluated. Objective: The main objective of this study was to evaluate risk factors for DGF and the impact of its occurrence and length on graft survival and function. Methods: A retrospective cohort study was performed in 517… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…Extended criteria donor (ECD) organs and organs recovered from donation after circulatory death (DCD), however, are more vulnerable to ischemia reperfusion injury. This eventually translates into higher rates of delayed graft function (DGF), primary non-function (PNF) and inferior graft survival [ 2 , 3 , 4 , 5 ]. While ECD kidneys have a 1.7 times greater risk for graft failure [ 6 , 7 ], recipients still gain a significant survival benefit compared to dialysis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extended criteria donor (ECD) organs and organs recovered from donation after circulatory death (DCD), however, are more vulnerable to ischemia reperfusion injury. This eventually translates into higher rates of delayed graft function (DGF), primary non-function (PNF) and inferior graft survival [ 2 , 3 , 4 , 5 ]. While ECD kidneys have a 1.7 times greater risk for graft failure [ 6 , 7 ], recipients still gain a significant survival benefit compared to dialysis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functions of the graft depend on the condition of the kidney prior to transplantation, cold/warm ischemia durations, and post-transplant graft perfusion [5]. The shorter the cold ischemia time, the better the long-term survival of the graft is [12]. In our study, the duration of cold ischemia was shorter than 24 hours in all cadaveric donors.…”
Section: Discussionmentioning
confidence: 52%
“…In the previously reported study from Turkey by Kara et al (10), there was no difference in graft survival and recipient survival between the groups with and without DGF in the 1st year. Helfer et al (7) determined that GFR was found to be statistically significantly higher in the group with DGF in the first 4 years after kidney transplantation, while 5 years later this difference was reduced and became insignificant. They demonstrated that longer DGF duration (>14 days) was associated with graft loss and worse kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, DGF has been associated with 38% increased risk of acute rejection and 41% increased risk of graft loss in an average follow-up of 3.2 years. While many studies have shown that DGF is associated with decreased graft survival and decreased recipient survival (7)(8)(9), some other studies was found no association between DGF and graft survival, although it was associated with reduced kidney function (10,11).…”
Section: Introductionmentioning
confidence: 99%